(untitled) (Socio-economic relations in the digital society, 2019)
The analysis of budgetary possibility of local budgets of Ukraine is in-process conducted and, in particular, areas of region of Carpathians. The level of financial firmness of local budgets, sufficientness of budgetary potential of region and his capability is analysed. The integral index of budgetary possibility of regions of Ukraine in 2012–2014 is certain. Rating of regions is formed on this index and the type of budgetary possibility is certain each of areas. Strengths and weaknesses of budgetary possibility of regions of Ukraine in 2014 are described. It is proved that formation of a stable income base of local budgets and expenditure of a balanced policy, and stimulate the interest of local governments to implement new approaches and use the experience of developed countries in the development of their regions and municipalities – a direct path to the formation of financially capable and independent developed regions and communities.